Medical conditions in the athlete - Cuppett, Micki; Flanagan, Katie Walsh (Human Kinetics, 2017)
Medical Conditions in the Athlete, Third Edition With Web Study Guide provides comprehensive medical information that assists health care providers and athletic trainers in recognizing and identifying underlying and potentially serious medical conditions that may affect their chosen course of treatment. The book addresses medical conditions by body system, their mechanism of acquisition, signs, symptoms, differential diagnoses, referral, treatment, and return-to-participation criteria. Also provides readers with research-driven assessment and treatment information for medical conditions that affect all types of athletes. It is a comprehensive textbook and an important reference for health care providers such as athletic trainers and physical therapists who work with active populations.